Life cycle carbon cost of buildings under carbon trading and carbon tax system in China. (March 2021) - Luo, Wei; Zhang, Yurong; Gao, Yuanlin; Liu, Yinshan; Shi, Chengcheng; Wang, Yuanfeng
Highlights: A building's life cycle carbon cost accounting model was developed. LIME model was used to test the validity and reliability of the carbon cost model. We provide references for conducting carbon trading and carbon tax in building sector. Abstract: Buildings contribute 23 % of the total CO2 emissions produced by global economics activities, in which nearly 41 % are emitted by China. Carbon accounting is necessary to support an efficient low-carbon economic system. There is currently very little research on the carbon cost of buildings, especially in China. This article analyzes the carbon emissions generated during the life cycle of buildings, and transfers them to building environment cost and carbon cost. A life cycle building carbon cost accounting model was proposed under different carbon cost systems, including carbon trading system and carbon tax system. To verify the validity and reliability of the proposed model, the similarities and differences between carbon cost and carbon emission environmental damage cost determined by the Life-cycle Impact Assessment Method based on Endpoint Modeling (LIME) were compared. Carbon costs can link carbon reduction with economic benefits, and push the present policy-based mandatory reduction measures to market-based means, which is of great significance to sustainable development of the construction industry and China's future emission reduction targets.